“The Painted Pottery Road” and Early Sino-Western Cultural Exchanges - Jianye, Han (Anabasis. Studia Classica et Orientalia, 2012)
“The Painted Pottery Road” as a concept was first proposed by Li Ji(李济)in 1960 and was used to sum up Johan Gunnar Andersson’s theory that “the Yangshao culture came from the West;” in other words, painted pottery is essentially western in origin. The “Painted Pottery Road” signifies the expansion and transmission of early Chinese culture, manifested in the form of painted pottery, westward from Shaanxi and Gansu, as well as the eastward movement of western culture. “The Painted Pottery Road” lasted from the fourth to the first millennium BC, during which four periods – c. 3500, c. 3000, c. 2200, and c. 1300 BC – characterize the westward expansion of painted pottery. Although numerous routes were used for its transmission, generally speaking they are grouped around the Qinghai-Tibetan Plateau as the North Road and the South Road, respectively. “The Painted Pottery Road” was thus the primary route of early Sino-Western cultural exchanges, serving as the precursor of “the Silk Road,” which subsequently exerted a great deal of influence on the formation and development of Chinese and Western civilization.